In vitro anti-bacterial activity of Tinospora cordifolia leaf extract and its phytochemical screening - Praiwala, B.; Priyanka, S.; Raghu, N.; Gopenath, N.; Gnanasekaran, A.; Karthikeyan, M.; Indumathi, R.; Ebrahim, N.K.; Pugazhandhi, B.; Pradeep, P.; Ranjith, M.S.; Balasubramanian, S.; et al. (Journal of Biomedical Sciences, 2019)
Background: Antimicrobial resistance is the main concern worldwide to combat infectious. Over the years studies on leaf extracts Tinospora cordifolia have demonstrated the potent role its antibacterial property. The current study is an attempt to test its antibacterial property against Escherichia coli cell division. Material and methods: Phytochemical screening assay of T. cordifolia leaf extract was done using standard procedure and the results showed the presence of alkaloid, carbohydrate, terpenoid, steroid, tannin, amino acid, flavonoid and glycoside components. Results: HPLC analysis revealed the presence of berberine in T. cordifolia leaf extract. Further E. coli cells were treated with berberine to study its efficacy in inhibiting cell division. Antibacterial assay was performed by using disc diffusion method. Conclusion: Among aqueous, methanolic, ethanolic, chloroform, hexane and acetone extract only methanolic extract showed zone of inhibition.